Psychometric Characteristic of Social Competence and Behaviour Evaluation (SCBE-30) in a Sample of Nigerian Preschoolers - A.A Adetunji; A.H Aliu; T.A Salami (Randwick International of Social Science Journal, 2022)
Social Competence and Behaviour Evaluation (SCBE-30) is a 3-factor (Externalizing, Internalizing and Social Competence) 30-item questionnaire that examines Preschoolers (Kindergarten and Nursery). The main goal of this study is the validation and adaptation of the scale in Nigeria. 400 pre-schoolers in Ile-Oluji, Ondo State, Nigeria are involved in the study while 364 children whose Parental Consent Form was obtained are the final participants. McDonald’s ωt (McDonald, 1999) measure of reliability using the psych package from CRAN (Revelle, 2008) was used to verify the internal consistency of the scale. The original subscale with 10 items of the novel SCBE-30 version is not confirmed by the confirmatory factor analysis. Seven items showed significant contribution to both SC and AW while all 10 items of the AA subscale have significant loadings. However, only 4 items for the SC scale showed factor loading of above 0.40, 3 for AW and 6 for AA. Exploratory factor analysis showed that boys are more aggressive than girls while girls exhibit more social competence and internalizing behaviour. The social competence scale is found to be significantly different from other factors while both Anger-Aggression and Anxiety-Withdrawal showed no difference. All inter-factor correlations agreed with the literature. Five models are compared using various modifications and the final accepted model have Chi-Square = 261.316; GFI = 0.946, CFI = 0.953, RMSEA = 0.027 and SRMR = 0.047. The new 24-item scale for the Nigerian sample shows good psychometric characteristics and meets validation criteria as reported by researchers where the scale had been earlier validated.